Are pressure injuries related to skin failure in critically ill patients?. Issue 5 (September 2018) - Nowicki, Jake L.; Mullany, Daniel; Spooner, Amy; Nowicki, Tracy A.; Mckay, Peta M.; Corley, Amanda; Fulbrook, Paul; Fraser, John F.
Abstract: Background: Pressure injuries contribute significantly to patient morbidity and healthcare costs. Critically ill patients are a high risk group for pressure injury development and may suffer from skin failure secondary to hypoperfusion. The aim of this study was to report hospital acquired pressure injury incidence in intensive care and non-intensive care patients; and assess the clinical characteristics and outcomes of ICU patients reported as having a hospital acquired pressure injury to better understand patient factors associated with their development in comparison to ward patients. Methods: The setting for this study was a 630 bed, government funded, tertiary referral teaching hospital. A secondary data analysis was undertaken on all patients with a recorded PI on the hospital's critical incident reporting systems and admitted patient data collection between July 2006 to March 2015. Results: There were a total of 5280 reports in 3860 patients; 726 reports were intensive care patients and 4554 were non-intensive care patients, with severe hospital acquired PI reported in 22 intensive care patients and 54 non-intensive care patients. Pressure injury incidence increased in intensive care patients and decreased in non-intensive care patients over the study period. There were statistically significant differences in the anatomical location of severe hospital acquired pressure injuries between these groups (p = 0.008). Conclusion: Intensive care patients have greater than 10-fold higher hospital acquired pressure injury incidence rates compared to other hospitalised patients. The predisposition of critically ill patients leaves them susceptible to pressure injury development despite implementation of pressure injury prevention strategies. Skin failure appears to be a significant phenomenon in critically ill patients and is associated with the use of vasoactive agents and support systems such as extra corporeal membrane oxygenation and mechanical ventilation.